DEVELOPMENT OF STUDENTS’ COMMUNICATIVE POTENTIAL - Galina A. Berulava; Emma M. Sagilyan (Высшее образование в России)
The article analyzes the problem of formation of productive communicative students’ behavior on the base of a new methodological platform of personal development 2 the theory of network education. The article reviews the influence of the information environment on the formation of personality communicative stereotypes. Formation of students’ communicative culture is basedon using a special speech repertoireduring systematic repeated training work.